Adjuvant nivolumab plus ipilimumab or nivolumab monotherapy versus placebo in patients with resected stage IV melanoma with no evidence of disease (IMMUNED): a randomised, double-blind, placebo-controlled, phase 2 trial - Zimmer, Lisa; Hassel, Jessica C.; Schadendorf, Dirk (The lancet, 2020)
Background - Nivolumab and ipilimumab, alone or in combination, are widely used immunotherapeutic treatment options for patients with advanced—ie, unresectable or metastatic—melanoma. This criterion, however, excludes patients with stage IV melanoma with no evidence of disease. We therefore aimed to evaluate the safety and efficacy of adjuvant nivolumab plus ipilimumab or nivolumab monotherapy versus a placebo in this patient population. - Methods - We did a randomised, double-blind, placebo-controlled, phase 2 trial in 20 German academic medical centres. Eligible patients were aged 18-80 years with stage IV melanoma with no evidence of disease after surgery or radiotherapy. Key exclusion criteria included uveal or mucosal melanoma, previous therapy with checkpoint inhibitors, and any previous immunosuppressive therapy within the 30 days before study drug administration. Eligible patients were randomly assigned (1:1:1), using a central, interactive, online system, to the nivolumab plus ipilimumab group (1 mg/kg of intravenous nivolumab every 3 weeks plus 3 mg/kg of intravenous ipilimumab every 3 weeks for four doses, followed by 3 mg/kg of nivolumab every 2 weeks), nivolumab monotherapy group (3 mg/kg of intravenous nivolumab every 2 weeks plus ipilimumab-matching placebo during weeks 1-12), or double-matching placebo group. The primary endpoint was the recurrence-free survival in the intention-to-treat population. The results presented in this report reflect the prespecified interim analysis of recurrence-free survival after 90 events had been reported. This study is registered with ClinicalTrials.gov, NCT02523313, and is ongoing. - Findings - Between Sept 2, 2015, and Nov 20, 2018, 167 patients were randomly assigned to receive nivolumab plus ipilimumab (n=56), nivolumab (n=59), or placebo (n=52). As of July 2, 2019, at a median follow-up of 28·4 months (IQR 17·7-36·8), median recurrence-free survival was not reached in the nivolumab plus ipilimumab group, whereas median recurrence-free survival was 12·4 months (95% CI 5·3-33·3) in the nivolumab group and 6·4 months (3·3-9·6) in the placebo group. The hazard ratio for recurrence for the nivolumab plus ipilimumab group versus placebo group was 0·23 (97·5% CI 0·12-0·45; p<0·0001), and for the nivolumab group versus placebo group was 0·56 (0·33-0·94; p=0·011). In the nivolumab plus ipilimumab group, recurrence-free survival at 1 year was 75% (95% CI 61·0-84·9) and at 2 years was 70% (55·1-81·0); in the nivolumab group, 1-year recurrence-free survival was 52% (38·1-63·9) and at 2 years was 42% (28·6-54·5); and in the placebo group, this rate was 32% (19·8-45·3) at 1 year and 14% (5·9-25·7) at 2 years. Treatment-related grade 3-4 adverse events were reported in 71% (95% CI 57-82) of patients in the nivolumab plus ipilimumab group and in 27% (16-40) of those in the nivolumab group. Treatment-related adverse events of any grade led to treatment discontinuation in 34 (62%) of 55 patients in the nivolumab plus ipilimumab group and seven (13%) of 56 in the nivolumab group. Three deaths from adverse events were reported but were considered unrelated to the study treatment. - Interpretation - Adjuvant therapy with nivolumab alone or in combination with ipilimumab increased recurrence-free survival significantly compared with placebo in patients with stage IV melanoma with no evidence of disease. The rates of grade 3-4 treatment-related adverse events in both active treatment groups were higher than the rates reported in previous pivotal trials done in advanced melanoma with measurable disease. - Funding - Bristol-Myers Squibb.
Gesehen am 23.09.2020